What Is the Meaning and Purpose of Risk Management in Cyber Security? - Dhaval Chudasama (International Journal of Information Security Engineering, 2025)
Organizations and their information systems are increasingly exposed to risk and uncertainty from a variety of sources, including computer fraud, espionage, and sabotage or cyber-attacks. The purpose of this article is to outline several steps, protocols, and factors that any organization should consider in the event of a cyber-attack. Over time, some damage causes, including denial of service or intrusion attacks, have grown more frequent, aggressive, and complex. Complete security is unattainable. For this reason, companies need to implement strategies and tactics that allow them to rank risks according to their impact and likelihood, which indicates a higher risk to the company. When preparing for possible cyber-attacks, it is important to understand the logical flow of actions that can be taken during an attack, to incorporate best practices, to assess the level of risk the organization faces and proactively design a handbook to respond to these situations.
Keywords: Cyber security; Cyber-attack; cyber risk analysis; incident response; risk management